Check me out [large type] - Wilhite, Becca., 1973- (Proper romance., 2019)
Greta loves her job as assistant librarian. She loves her best friend, Will, the high school civics teacher and debate coach. She even loves her mother despite her obvious disappointment that Greta is still single. Then she meets Mac in the poetry section of the library, and she is smitten. Mac is heart-stoppingly gorgeous and showers her with affection, poetic text messages, and free hot chocolate at the local café where he works. The only problem is that he seems to be a different person in his texts than in his face-to-face conversation. When the Franklin Library is threatened with closure, Greta leaps into action. She arranges for a "battle of the bands" book jam, hosts a book signing by a famous author, and finally, stages a protest that raises more than a few eyebrows. Through it all, she slowly realizes that it is Will, not Mac, who she turns to for support and encouragement. Mac has the looks; Will has the heart. How can she choose between them? Check Me Out is a contemporary romance--with just a hint of Cyrano de Bergerac--that reminds us that it is what's on the inside that matters most.